Innovations in AI-Powered Healthcare: Transforming Cancer Treatment with Innovative Methods - Saad Rasool; Mohammad Ali; Hafiz Muhammad Shahroz; Hafiz Khawar Hussain; Ahmad Yousaf Gill (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Abstract: In this thorough review, we explore the multifaceted role of artificial intelligence (AI) in cancer medicine, highlighting its potential applications, challenges, and future directions. Artificial intelligence (AI) holds enormous promise for revolutionizing patient care and improving outcomes when integrated into various aspects of cancer medicine, including drug discovery and development, early detection and screening, and drug discovery. AI-driven methods in early detection and screening can increase sensitivity, decrease false-positive rates, and provide personalized risk assessment, which can boost the efficacy and efficiency of cancer screening programs. However, issues like algorithm bias, data quality, and regulatory compliance need to be resolved before AI can be fully utilized in this field. In addition, AI-driven drug discovery and development offers chances to speed up target identification, repurpose current medications, and create new therapeutics with improved safety and efficacy profiles. However, even with AI's potential to speed up drug discovery, issues with data accessibility, algorithm interpretability, and ethical implications still exist. Researchers, clinicians, regulators, and industry stakeholders must work together to develop strong data-sharing initiatives, ethical guidelines, and governance frameworks in order to address these challenges. By putting patient-centered approaches first, integrating multi-modal data, and encouraging interdisciplinary collaboration, we can harness the transformative power of AI to speed up the translation of research findings into novel therapies and enhance global cancer patient outcomes.